The Moderating and Mediating effects of Low Income and feelings of Perceived Deprivation on Madrassa Students - Ali Khan Ghumro; Humera Hakro; Anwar Mustafa, (Progressive Research Journal of Arts & Humanities (PRJAH), 2024)
Religious education in the country like Pakistan is considered mandatory and when it comes to make for life choices, majority of the parents chose religious education. Hence, majority madrassas students come from poor background because they cannot afford or acquire education in general subjects, compared to kids of their age studying in private and government schools which leads to feelings of perceived deprivation. To measure the impact of such deprived feelings on the madrassa students, this study applied quantitative method to examine the impact of perceived feelings. Out of 283 registered madrassas, 40 were selected randomly, whereas, 25 Questionnaires were distributed to each madrassa. The model was tested using structural equation modeling to examine the effects of low and high income, and the mediating impact of perceived deprivation on the criterion constructs. The moderating effects of low income indicate that six out of nine hypotheses were found significant; whereas the results for the impact of high income on criterion constructs demonstrate that out of the nine hypothesized relationships, only four were found significant. Nevertheless, the effects of perceived deprivation (mediation) demonstrate that the mediation with funding, religious gatherings and ethnic and religious affiliation have significant effects on the radicalization. On the other hand, the mediation effects between syllabus and radicalization were found statistically non-significant.